TEACHER’S PERCEPTION OF SELF-DIRECTED LEARNING AND EFL STUDENTS’ LEARNING AUTONOMY DURING COVID-19 PANDEMIC - Yanti, Made Dama; Artini, Luh Putu; Wahyuni, Luh Gede Eka (Universitas Pendidikan Ganesha, 2021)
The COVID-19 pandemic has forced academic institutions in Indonesia to implement online learning. As a result, teachers must prepare online learning strategies that can build students’ independent learning. This study aims to analyze teacher perceptions of independent learning, assigned activities in online learning, and independent learning components in activities. This study uses an embedded mixed-method approach. The methods used to collect data are observation, interviews, and questionnaires. The instruments used to collect data are self-rated questionnaires, observation tables, and classification tables. The technique used in analyzing the data is descriptive qualitative and quantitative statistics. The results of this study indicate that teachers feel they have knowledge about and in implementing Independent Learning. The teacher carries out the learning process in three parts: pre-activity, initial activity, and post-activity. However, there are only three components of Self-Directed Learning that are included in the action. In its activities, self-directed learning is when the teacher provides material, individual assignments, and assistance when needed. However, independent learning is no longer a reflection on post-activity because there is no feedback. Therefore, more effective and exciting learning activities are required.